Feasibility Study of Black Garlic's Home Industry in Ngestiharjo Village - Purwaditya, Anjar Kistia; Muliana, Noor Aulia Asrul; Shahrul, Reza Ulfi; Anoraga, Satria Bhirawa (Journal of Agri-Food Science and Technology, 2021)
Garlic production in Indonesia is quite large. So far, we have known that many garlic are sold raw without being processed. But lately garlic is widely developed processing garlic into other products like black garlic that being produced by Mrs. Vetie Kusumaningsari, S.E. in Yogyakarta. The objective of this study is to analyze the feasibility of Black Garlic's Home Industry. The method being used in this study are break even point (BEP), net present value (NPV), benefit/cost (B/C) ratio, and payback period to analyze the data being collected. The result of this study indicates that BEP can be reached 334 cups product, with 7% of interest NPV indicate positive at Rp 10.713.817,8, B/C ratio was at 0,7 and payback period (PP) at 0,045 year. In conclusion regarding to the study, black garlic's home industry feasible to run and develop.